A Study on Correlation Between Human Resource Practices and Employee Engagement among Selected Banks’ Employees - Abdullah, Nor Hazana; Muhamed Yusof, Muhamad Hafizuddin (Research in Management of Technology and Business, 2022)
Human Resource practices plays as a vital role to the organization especially in banking sector as it is one of the influential economic contributors to the Malaysian’s economy. However, this sector is facing dynamic challenges that could affect the engagement among the employees. As effective human resource management practices play critical roles in ensuring employees’ engagement, this study is to investigate the relationship between HR practices and employee engagement. This study was using quantitative approach by distributing questionnaires to selected banks’ employees in Kedah, Johor, Pahang. It was found that Selection & Recruitment is significantly correlated with employee engagement at r=0.74 (p<0.001), followed by Training & Development at r=0.625 (p<0.001) and Compensation at 0.581 (p<0.001). This finding implies the importance of human practices in ensuring employees’ engagement.